Comparative Morphology and Morphometry of Six Biotypes of Bemisia tabaci (Hemiptera: Aleyrodidae) from China - Jing-jing LI; Qing-bo TANG; Run-e BAI; Xiao-min LI; Jin-wei JIANG; Qing ZHAI; Feng-ming YAN (Journal of Integrative Agriculture, 2013)
Morphology and morphometry of six biotypes (B, Q, Cv, ZHJ-1, ZHJ-2 and ZHJ-3) of Bemisia tabaci (Gennadius) from China on cotton plants were studied by using microscopes. Nymphal body sizes and characters were measured and observed, especially on the 4th instar (pupal case), including the vasiform orifice, operculum, lingula, length and thickness of anterior and posterior wax margins, width of thoracic tracheal combs. Adult characters of both sexes were investigated including the body size, compound eyes, antennal segments, vasiform orifice, hind tarsi and genitals. The results indicated that differences of some morphological characters or morphometrics were significant among the six biotypes of B. tabaci in China: (1) Pupal sizes of the exotic biotypes (B and Q) were significantly larger than the indigenous biotypes with the following order as B>Q>ZHJ-1>Cv>ZHJ-3>ZHJ-2; (2) for both male and female adults, sizes of all characters investigated in the invading biotypes (B and Q), especially B, were much larger than those of the indigenous ones.